Sanksi Pidana Terhadap Pelecehan Lambang Negara - Ayou Lestari Duarkossu; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Interpretasi Hukum, 2021)
The coat of arms is a representation of the country itself. Since the first, cases of abuse of state symbols often occur. So in this case, a firm criminal act is needed in an effort to minimize the case. The purposes of this study are to review law enforcement against harassment of state symbols and criminal sanctions against harassment of state symbols. This research method uses a normative legal research type with a statutory approach. The technique of obtaining legal materials in this research is done by document study and literature study. Sources of legal materials used are primary, secondary and tertiary sources of legal materials. The method used in processing and in data analysis used in this study is qualitative. The results of the study indicate that sanctions/law enforcement against harassment of state symbols in Indonesia are law enforcement as TNI/POLRI and the government is tasked with maintaining the security of the community and the state. So that there are no crimes of criminal acts committed by the community, and in order to bring order to security in the midst of society. Criminal sanctions due to criminal acts can be in the form of imprisonment and fines in accordance with the provisions stipulated in the laws and regulations regarding harassment of the Indonesian state symbol.